Afatinib for the Treatment of Non-Small Cell Lung Cancer Harboring Uncommon EGFR Mutations: An Updated Database of 1023 Cases Brief Report - Yang, James Chih-Hsin; Schuler, Martin; Popat, Sanjay; Miura, Satoru; Park, Keunchil; Passaro, Antonio; De Marinis, Filippo; Solca, Flavio; Märten, Angela; Kim, Edward S. (Frontiers in Oncology, 2022)
Introduction: Previously, we developed a database of 693 patients with NSCLC and uncommon EGFR mutations treated with afatinib. Here, we provide an update of >1000 patients, with more data on specific mutations. Methods: Patients were identified from a prospective database developed by Boehringer Ingelheim and via literature review. Mutations were categorized as T790M-positive, exon 20 insertions, major uncommon (G719X, L861Q, S768I) and ‘others’. Patients with compound mutations (≥2 EGFR mutations) were analyzed separately. Key endpoints were time to treatment failure (TTF) and objective response rate (ORR). Results: Of 1023 patients included, 587 patients were EGFR TKI-naïve and 425 were EGFR TKI-pretreated. The distribution of mutation categories was: major uncommon (41.4%); exon 20 insertions (22.3%); T790M (20.3%); and ‘others’ (15.9%); 38.6% had compound mutations. Overall, median TTF (TKI naïve/pretreated) was 10.7 and 4.5 months. ORR was 49.8% and 26.8%, respectively. In TKI-naïve patients, afatinib demonstrated activity against major uncommon mutations (median TTF: 12.6 months; ORR: 59.0%), ‘other’ mutations (median TTF: 10.7 months; ORR: 63.9%) including strong activity against E709X (11.4 months; 84.6%) and L747X (14.7 months; 80.0%), and compound mutations (11.5 months; 63.9%). Although sample sizes were small, notable activity was observed against specific exon 20 insertions at residues A763, M766, N771, and V769, and against osimertinib resistance mutations (G724S, L718X, C797S). Conclusion: Afatinib should be considered as a first-line treatment option for NSCLC patients with major uncommon, compound, ‘other’ (including E709X and L747X) and some specific exon 20 insertion mutations. Moderate activity was seen against osimertinib resistance EGFR mutations.